ANALISIS TINGKAT VALIDITAS MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MICROSOFT POWERPOINT PADA MATERI BANGUN DATAR KELAS IV SD - Rima Lutfiyani; Sumadi; Ina Agustin (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2026)
This study aims to create Microsoft PowerPoint-based interactive learning media and test its feasibility level for mathematics subjects, specifically geometry materials for fourth-grade elementary school students. The research method used is Research and Development (R&D) following the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data collection instruments included validation sheets assessed by three expert validators: media experts, language experts, and material experts. The results of the data analysis showed that the validity level of the learning media from media experts reached 97%, categorized as "Very Valid". Validation from language experts obtained a percentage of 86%, categorized as "Very Valid" and validation from material experts also reached 94%, categorized as "Very Valid". Based on these assessment results, it can be concluded that the Microsoft PowerPoint-based interactive learning media for geometry material has met the feasibility criteria with a "Very Valid" predicate and is ready to be implemented as an innovative solution in the learning process for fourth-grade elementary school.